Heterogeneous tissue distribution of a mitochondrial DNA polymorphism in heteroplasmic subjects without mitochondrial disorders. Issue 5 (1st May 2001) - Kirches, Elmar; Michael, Matthias; Warich-Kirches, Michaela; Schneider, Thomas; Weis, Serge; Krause, Guido; Mawrin, Christian; Dietzmann, Knut
Abstract : CONTEXT: Several maternally inherited point mutations of the mitochondrial genome cause mitochondrial disorders, but the correlation between genotype and phenotype remains obscure in many cases. The same mutation may cause various diseases, probably because of a different tissue distribution. OBJECTIVE: To assess the role of random somatic segregation in generating interperson differences by analysis of an apparently neutral polymorphism. DESIGN: Screening of 81 brain samples from subjects without mitochondrial disorders and selection of five necropsy cases showing a high level of heteroplasmy for the polymorphism. MAIN OUTCOME MEASURES: A proportion of various distinct genotypes in the mtDNA pool of the tissues, identified by fluorescent PCR products, representing a short polycytosine tract of variable length in the mitochondrial displacement loop. RESULTS: Differences were found between organs or groups of organs within subjects, pointing towards somatic segregation of mtDNA. In addition, marked differences of this organ distribution occurred between subjects, which cannot be explained by tissue specific selection. CONCLUSIONS: The observed interperson differences can be explained by somatic segregation, which occurs randomly at various developmental stages. Besides tissue specific selection, this process might participate in the distribution of pathogenic mtDNA mutations.